Answer:
There is no point of the form (-1, y) on the curve where the tangent is horizontal
Step-by-step explanation:
Notice that when x = - 1. then dy/dx becomes:
dy/dx= (y+2) / (2y+1)
therefore, to request that the tangent is horizontal we ask for the y values that make dy/dx equal to ZERO:
0 = ( y + 2) / (2 y + 1)
And we obtain y = -2 as the answer.
But if we try the point (-1, -2) in the original equation, we find that it DOESN'T belong to the curve because it doesn't satisfy the equation as shown below:
(-1)^2 + (-2)^2 - (-1)*(-2) - 5 = 1 + 4 + 2 - 5 = 2 (instead of zero)
Then, we conclude that there is no horizontal tangent to the curve for x = -1.
Answer:
<em><u>-</u></em><em><u>1</u></em><em><u>0</u></em><em><u>.</u></em><em><u>2</u></em>
Step-by-step explanation:
<u>f</u><u>{</u><u>5</u><u>}</u> = <u>6</u><u>(</u><u>5</u><u>^</u><u>2</u><u>)</u><u> </u><u>+</u><u> </u><u>2</u><u>(</u><u>5</u><u>)</u><u> </u><u>-</u><u> </u><u>7</u>
g{-3}= 4(-3)-3
= <u>6</u><u>(</u><u>2</u><u>5</u><u>)</u><u> </u><u>+</u><u> </u><u>1</u><u>0</u><u> </u><u>-</u><u> </u><u>7</u>
-12 - 3
= <u>150</u><u> </u><u>+</u><u> </u><u>1</u><u>0</u><u> </u><u>-</u><u> </u><u>7</u>
- 15
= <u>1</u><u>5</u><u>3</u>
-15
= <u>-</u><u>5</u><u>1</u>
5
= <em><u>-</u></em><em><u>1</u></em><em><u>0</u></em><em><u>.</u></em><em><u>2</u></em>
<span>Traveled Downstream a distance of 33 Mi and then came right back. If the speed of the current was 12 mph and the total trip took 3 hours and 40 minutes.
Let S = boat speed in still water then (s + 12) = downstream speed (s -12) = upstream speed
Given Time = 3 hours 40 minutes = 220 minutes = (220/60) h = (11/3) h Time = Distance/Speed
33/(s +12) + 33/(s-12) = 11/3 3{33(s-12) + 33(s +12)} = 11(s+12) (s -12) 99(s -12 + s + 12) = 11(</span> s^{2} + 12 s -12 s -144) 99(2 s) = 11(s^{2} -144) 198 s/11 = (s^{2} -144) 18 s = (s^{2} -144) (s^{2} - 18 s - 144) = 0 s^{2} - 24 s + 6 s -144 =0 s(s- 24) + 6(s -24) =0 (s -24) (s + 6) = 0 s -24 = 0, s + 6 =0 s = 24, s = -6 Answer) s = 24 mph is the average speed of the boat relative to the water.
Those are the answers
2x-2
6x+9
7x+35
10x-5y
Answer:
Answer: 3x + 3 = 2x + 1
Answer: 3x + 3 = 2x + 1 <=>3x - 2x = 1 - 3
Answer: 3x + 3 = 2x + 1 <=>3x - 2x = 1 - 3 <=> x = -2